Data from salivary gland proteome analysis of female Aedes aegypti Linn - Rakhi Dhawan (Data in Brief, 2017)
Salivary gland proteins from female Aedes aegypti mosquito were extracted and analyzed on high-resolution mass spectrometry. Proteomic data was analysed using two search algorithms SEQUEST and Mascot, which results in acquisition of 83,836 spectra which were assigned to 5417 peptides belonging to 1208 proteins.These proteins were then assigned molecular functions and further analysis revealed biological processes they are involved in using Gene Ontology annotations. Several immunity related pathways were found to be enriched in salivary gland.The data of this study are also related to the research article “Mosquito-Borne Diseases and Omics: Salivary gland proteome of the female Aedes aegypti mosquito” (Dhawan et al., 2017) [1]. These data are deposited in ProteomeXchange in the public dataset PXD002468. In addition,a scientific interpretation of this dataset by Dhawan et al. [1] is available at http://dx.doi.org/10.1089/journal.omi.2016.0160. Keywords: Proteomics, Salivary gland, Immunogenic, Vectorborne Diseases, Aedes aegypti, Protein–protein interactions